Psychosocial Interventions for Amphetamine Type Stimulant Use Disorder: An Overview of Systematic Reviews - Tran, Mai Thi Ngoc; Luong, Quang Hung; Le Minh, Giang; Dunne, Michael P.; Baker, Philip (Frontiers in Psychiatry, 2021)
Introduction: Amphetamine-type stimulants (ATS) use is a global concern due to increased usage and the harm to physical, mental, and social well-being. The objective of this overview of systematic reviews is to summarise trial results of psychosocial interventions and describe their efficacy and safety. Methods: We searched seven bibliographic databases to November 2020 for systematic reviews examining ATS misuse treatment by psychosocial interventions. Given the apparent incompleteness of the included reviews, we undertook a supplemental meta-analysis of all eligible primary studies. Results: We included 11 systematic reviews of moderate to high quality and 39 primary studies which assessed the outcomes of psychosocial interventions on people who use ATS. The key findings include: (1) There were conflicting results about the effectiveness of psychosocial interventions among reviews, which may confuse decision-makers in selecting treatment. (2) In the supplemental meta-analysis, relative to usual care (only counselling or self-help materials), membership of a psychological intervention group was associated with an important reduction in drug usage [risk ratio (RR) 0.80, 95% CI: 0.75 to 0.85]. Patients in psychological interventions used injectables substantially less [odds ratio (OR) 0.35, 95% CI: 0.24 to 0.49]. The risk of unsafe sex in the psychosocial intervention group was lower than in the control group (RR 0.49, 95% CI: 0.34 to 0.71). The combination of therapies reduced 1.51 day using drugs in the preceding 30 days (95% CI: −2.36 to −0.67) compared to cognitive behavioural therapy intervention alone. (3) Compared to usual care, cognitive behavioural therapy was less likely to be retained at follow-up (RR 0.89, 95% CI: 0.82 to 0.97; high-quality evidence). However, the additional of contingency management strategy can make an important improvement upon retention (RR 1.42, 95%CI: 1.25 to 1.62). Authors' Conclusions: Integrated models are more effective than a single-treatment strategy. Comprehensive and sustained psychosocial interventions can help to reduce use of ATS and other drugs, risk behaviours and mental disorders, and significantly improve treatment adherence.